2021
DOI: 10.1186/s40348-021-00120-0
|View full text |Cite
|
Sign up to set email alerts
|

The mutual patterning between the developing nephron and its covering tissues—valid reasons to rethink the search for traces left by impaired nephrogenesis

Abstract: Background The impairment of nephrogenesis can cause the termination of nephron formation in preterm and low birth weight babies. This leads to oligonephropathy with severe health consequences in later life. Although many clinical parameters are known, surprisingly little information is available regarding the initial damage on the developing nephron. Equally astounding, the first morphological data regarding the specifics of nephron formation in the nephrogenic zone of the fetal human kidney d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…4d). Recent investigations additionally demonstrated that each of the listed stages exhibits a different shape, is recognized within personal coordinates, and is facing individual parts of the structural neighbors [12,19,20]. This again shows that each stage of nephron anlage is exposed to a typical claim of the interjacent interstitium, which can exhibit existing, evolving, transient, degrading, or lasting properties (Fig.…”
Section: Translocation Between Interstitial Workbenchesmentioning
confidence: 88%
See 2 more Smart Citations
“…4d). Recent investigations additionally demonstrated that each of the listed stages exhibits a different shape, is recognized within personal coordinates, and is facing individual parts of the structural neighbors [12,19,20]. This again shows that each stage of nephron anlage is exposed to a typical claim of the interjacent interstitium, which can exhibit existing, evolving, transient, degrading, or lasting properties (Fig.…”
Section: Translocation Between Interstitial Workbenchesmentioning
confidence: 88%
“…From the kidneys of preterm and low birth babies, it is known that noxae provoke the reduction in width of the nephrogenic zone [6]. Although it has not been closely investigated, one must assume that the loss of tissue concerns not only the stages of nephron anlage but also the structural neighbors such as the CD ampullae, the sprouting microvessels, the establishing interstitium, and probably also the renal capsule [12]. As a consequence, it is highly important to develop a deeper understanding of these details, when the interstitium is seen as an instance that masters the formation of a nephron or when this process is harmed by the noxae impairing nephrogenesis [4,14,21,24].…”
Section: Narrow Interstitial Cleft At the Medial Aspect Of The Develo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated the development of the tubular portion and the entire nephron from different perspectives [Osathanondh and Potter, 1966;Saxén and Sariola, 1987;Dakovic-Bjelakovic et al, 2005;Faa et al, 2012;Song et al, 2012;Minuth, 2021]. However, only one study quantified the development of renal tubules in the kidney cortex of human foetuses at different GAs and reported a gradual increase in their volume density [Dakovic-Bjelakovic et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of Ki-67, Bcl-2, and Bax have been investigated in developing nephrons allocated to the nephrogenic, maturation, and mature zones of the foetal kidney cortex [Minuth, 2020[Minuth, , 2021. The distribution and staining intensity of immunopositive cells were independently assessed by 2 pathologists in all cases.…”
Section: Immunohistochemical Methodsmentioning
confidence: 99%